Effect of Carica papaya raw fruit extract using in vitro rat uterus preparations - Chaganti Nagesh; Narapogu, Venkatanarayana; Rajendra Kumar; Ksheerasagar, Vinay Kumar (Asian Journal of Medical Sciences, 2023)
Background: Uterine stimulants are medications used to induce/augment labor, induce abortion, and to prevent postpartum hemorrhage. Currently, available drugs carrying adverse effects, hence the present study is designed to study the effect of Carica papaya raw fruits extract in comparison with oxytocin using in vitro rat uterus preparations. Aims and Objectives: Primary and secondary aims of the present study were to evaluate the uterine stimulant effect and also the potency of C. papaya fruit extract using in vitro rat uterus preparations in comparison with oxytocin. Materials and Methods: A total of 6 female rats were taken and anesthetized with ether. By giving midline incision at abdomen from pubic symphysis, two horns of uterus were identified and collected from each rat. Uterus of each rat was subjected to Oxytocin 0.32 IU (standard), alcoholic extract of C. papaya 0.32 mg (AECP), and combination of various doses of AECP (0.64 mg, 1.28 mg, and 2.56 mg) and a fixed dose of Oxytocin (0.32 IU). Using Sherrington’s kymograph, the uterine responses of each drug and combinations were studied in terms of height of the graph. Results: The mean contraction of uterus was 6.55mm and 2.26 cm, when Oxytocin (0.32 UI) and AECP (0.32 mg) injected, respectively. When combination of Oxytocin and different doses of AECP was injected, the uterus has shown dose-dependent response, i.e., 7.13 cm (Oxytocin 0.32 IU +AECP 3.2 mg), 8.08 cm (Oxytocin 0.32 IU + AECP 6.4 mg), and 9.01 cm (Oxytocin 0.32 IU + AECP 12.8 mg). Conclusion: AECP has shown dose-dependent uterine stimulant effect. Further studies are required to find out the possible mechanism behind the uterine stimulant activity of AECP.